2016
DOI: 10.1111/jan.13026
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative systematic review of the effects of non‐pharmacological interventions on reducing apathy in persons with dementia

Abstract: Study results demonstrate promise for the use of non-pharmacological interventions, particularly music-based interventions, in reducing apathy levels in individuals with dementia. Intervening to reduce apathy may have a positive clinical impact and healthcare providers should be encouraged to incorporate positive sources of interest and intellectual stimulation into care. However, future research is needed to examine the aetiologic mechanism and predictors of apathy, to improve evidence-based interventions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 64 publications
(339 reference statements)
1
46
0
Order By: Relevance
“…The chief tools for evaluating methodological quality of primary studies were derived from Cochrane, Centre for Evidence-Based Medicine (CEBM), and the Centre for Evidence-Based Physiotherapy (PEDro). One review (Goris et al, 2016) did not report sample size, so we found it by reading original studies. Table S1 elaborates the characteristics of the included reviews.…”
Section: Characteristics Of the Included Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chief tools for evaluating methodological quality of primary studies were derived from Cochrane, Centre for Evidence-Based Medicine (CEBM), and the Centre for Evidence-Based Physiotherapy (PEDro). One review (Goris et al, 2016) did not report sample size, so we found it by reading original studies. Table S1 elaborates the characteristics of the included reviews.…”
Section: Characteristics Of the Included Reviewsmentioning
confidence: 99%
“…A meta-analysis by Tsoi et al (2018) concluded that receptive music was more efficacious compared with interactive music. Goris et al (2016) mentioned music therapy was the strongest non-pharmacological method to reduce apathy. Moreover, for those with severe dementia, Lane-Brown and Tate (2009) implied music therapy was the most effective.…”
Section: An Overview Of Systematic Reviews Of Non-pharmacological Intmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-pharmacological interventions exist that address older adults’ cognitive and physical function as well as their social conditions, and have had inconsistent results; these interventions include physical activity, exercise, social interaction and engagement, cognitive stimulation, music, art therapy, reminiscence therapy, and caregiver interventions (Cohen-Mansfield, Marx, Dakheel-Ali, & Thein, 2015; Goris, Ansel, & Schutte, 2016). Multimodal strategies tailored to the individual appear most successful, but can be resource intensive (Cohen-Mansfield et al, 2015), which is problematic because of health care manpower shortages in a variety of settings (American Health Care Association, 2012; Harrington, Schnelle, McGregor, & Simmons, 2016).…”
mentioning
confidence: 99%
“…Non-pharmacological approaches have demonstrated evidence in improving levels of apathy, including; music based; art; cognitive stimulation; and reminiscence therapy (Goris, Ansel, & Schutte, 2016). Reminiscence therapy is commonly used in residential aged care and involves the discussion of a person's past experiences involving the use of items including photographs, magazines, or music (Westphal, Callega, LoGiudice, & Lautenschlager, 2017).…”
Section: Introductionmentioning
confidence: 99%